UV‐Sensitive Wearable Devices for Colorimetric Monitoring of UV Exposure. Issue 6 (17th January 2020) - Kurz, Wolfgang; Yetisen, Ali K.; Kaito, Mihai Valer; Fuchter, Matthew J.; Jakobi, Martin; Elsner, Martin; Koch, Alexander W.
Abstract: The extensive exposure of the human epidermis to solar radiation creates a health risk that results in skin cancer. Commercial sunscreens offer sufficient protection from ultraviolet (UV) radiation; however, the ability to determine UV exposure limits can provide informed decisions about the dose of sunscreen required and the frequency of re‐application. Here, a wide range of wearable devices that colorimetrically report on UV exposure are developed. Under UV radiation, UV‐sensitive dyes change their color from 280 to 400 nm in the visible spectrum. By correlating the current color value and the UV dose, the amount of sun exposure is determined with an accuracy of 95%. A smartphone camera algorithm is coded to automatically perform the color analysis of these dyes. The UV‐sensitive dyes are incorporated in wearable devices, skin patches, textiles, contact lenses, and tattoo inks. The developed wearable devices will ensure monitoring UV radiation to rationally manage the user's behavior in order to prevent harmful sun exposure. Abstract : UV‐sensitive wearable devices in the form of skin patches, textiles, contact lenses, and tattoo ink are developed to monitor solar radiation. The UV‐sensitive devices are based on leuco dyes that change their color from the UV to visible ranges of the spectrum. A smartphone camera algorithm and user interface are created to obtain quantitative measurements from the UV‐sensitive wearable devices.